Prevalence of piriformis syndrome and its associated risk factors among university students in Pakistan: a cross-sectional study - Hassan N Moafa; Nusrat Batool; Naila Azam; Azka Hafeez; Humaira Mehmood; Nimbal Imtiaz; Waqas A Shehzad; Asaad Saleem Malik; Ajiad Alhazmi; Manal Almalki; Almutasim B Moafa; Jobran M Moshi (BMJ Open)
Objective To determine the prevalence of piriformis syndrome (PS) among undergraduate university health sciences students aged 18 to 25 and assess the significant predictors of PS regardless of its type and severe PS in particular.Design A cross-sectional study.Setting The study was conducted at a tertiary care hospital of a public university in Pakistan from December 2023 to May 2024.Participants A total of 190 subjects enrolled in the study who met the eligibility criteria, which included being an undergraduate health sciences student (medical and allied health specialities), aged 18 up to 25 years, and willing to participate in the study. Participants were selected using multistage random sampling.Primary and secondary outcome measures The prevalence of PS in addition to associated risk factors as a primary outcome measures. Secondary outcome measures included the severity of PS.Results Of the total, 119 (62.6%) were female, 114 (60.0%) were between 22 and 25 years old, and 125 (65.8%) had standard body mass index. The prevalence of PS was (61.1%), whereas half suffered from severe PS, and the remaining half had mild and moderate PS. We found that factors such as casual sitting positions, sitting duration and International Physical Activity Questionnaire (IPAQ) score (physical activity) were associated with odds of PS in the crude and adjusted regression analyses. When stratified by severity of PS, factors such as writing positions, casual sitting positions, sitting duration and IPAQ score (physical activity) were associated with odds of severe PS in the crude and adjusted regression analyses.Conclusions Students have a high prevalence of PS, with an increased likelihood of buttock pain associated with prolonged sitting, poor posture and physical inactivity. Future research that includes several factors related to students’ social and psychological backgrounds is required.